Almond Blossom Snow The ballet music of Denis ApIvor - Jackson, Paul R. W. (Dance Books Ltd., Alton,Hampshire (UK), 2008)
The reputation of Denis IpIvor who died on 27 may 2004 has sunk to such a low level that most musicians do not even know his name. He has no entry in the New grove Dictionary of Music and Musicians, none of his music is available on record, nor has any of it been played on the BBC for many years. He is most likely to be remembered by balletomanes of a certain vintage for his scores which leapt screaming onto the complacent ballet stage of the 1950s. Ten years ago I spent two days with ApIvor at his home in Saltdean and this article is based on those reminiscences and on information from letters he subsequently wrote to me. In have left intact many of his comments since they do give a good impression of the man. It must be said that ApIvor felt very badly treated by Covent Garden and Sadler's Wells and this certainly coloured his views on many of the choreographers and directors associated with those organisations.